2006
DOI: 10.1007/s11373-006-9083-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant originated glycoprotein has anti-oxidative and anti-inflammatory effects on dextran sulfate sodium-induced colitis in mouse

Abstract: SummaryWe investigated the preventive effect of glycoprotein (27 kDa) isolated from Gardenia jasminoides Ellis (GJE) fruits on colitis in dextran sulfate sodium (DSS, 3%)-induced A/J mice which were administrated orally for 7 days. Anti-inflammatory activity of GJE glycoprotein was assessed by neutrophil infiltration and colonic lipid peroxidation, and determined by myeloperoxidase (MPO) activity and levels of thiobarbituric acid reactive substances (TBARS), respectively in DSS treatment system. The activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…Different studies reported that curcumin from C. longa reduced Cox-2 level [22,32,36]. Another herbal therapy with this effect is G. jasminoides [38].…”
Section: Effects On Cyclooxygenase (Cox)mentioning
confidence: 97%
See 2 more Smart Citations
“…Different studies reported that curcumin from C. longa reduced Cox-2 level [22,32,36]. Another herbal therapy with this effect is G. jasminoides [38].…”
Section: Effects On Cyclooxygenase (Cox)mentioning
confidence: 97%
“…It was demonstrated that some herbal therapies can ameliorate IBD by their antioxidant activity. Zataria multiflora [29], curcumin from C. longa [22,31,32,47], Ziziphora clinopoides [33], Ginkgo biloba [35,37], essential oil of Satureja khuzestanica [34], glycoprotein from Gardenia jasminoides [38], ethanolic extract and nicotine from Nicotiana tabacum [42], and polysaccharide from Rheum tanguticum [61,62] were shown to reduce indicators of lipid peroxidation, including thiobarbituric acid reactive substances (TBARS), myeloperoxidase (MPO), and/or malondialdedyde (MDA) in animal models of IBD. Some of them, such asG.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the activities of catalase, superoxide dismutase and glutathione peroxidase were increased after a supplement of GJE glycoprotein. Present investigation suggests that GJE glycoprotein is a potential therapeutic agent for ulcerative colitis [28].…”
Section: Plant-originated Glycoprotein Has Anti-oxidative and Anti-inmentioning
confidence: 88%
“…neutrophil infiltration and colonic lipid peroxidation due to its scavenging property. 98 A novel anti-oxidant water-soluble polysaccharide was isolated from Gardenia jasminoides Ellis proved significant scavenging abilities. 99 …”
Section: Anti-oxidant Activitymentioning
confidence: 99%